2012
DOI: 10.1111/j.1365-2109.2012.03132.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of stocking density and presence or absence of soil base on growth, weight variation, survival and body composition of pearlspot,Etroplus suratensis(Bloch) fingerlings

Abstract: With the objective to develop an indoor tank seed rearing system for pearlspot (Etroplus suratensis), effects of three stocking densities in presence or absence of soil base were evaluated on growth, weight variation, survival and body composition in a 60‐day trial. The experiment had a 3 × 2 factorial design with three levels of stocking density (150, 300 and 450 fish m−3) and two levels of soil base (with and without) in triplicates. Pearlspot fry (27.5 ± 0.5 mm/0.39 ± 0.02 g) were stocked in experimental ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
1
16
0
3
Order By: Relevance
“…Concentrations of toxic metabolites like nitritenitrogen (NO2-N)and ammonia-nitrogen (NH4-N) remained lower than the critical level and concentrations of nutrients like nitrate-nitrogen (NO3-N) and phosphate-phosphorous (PO4-P) was much lower than fertilized ponds reported from Sundarbans [4,28] and corroborated with those reported earlier by Mondal et al [29] from the same location. Lower nutrient concentrations in the studied extensive system may be attributed to complete dependence on natural productivity without any additional input.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Concentrations of toxic metabolites like nitritenitrogen (NO2-N)and ammonia-nitrogen (NH4-N) remained lower than the critical level and concentrations of nutrients like nitrate-nitrogen (NO3-N) and phosphate-phosphorous (PO4-P) was much lower than fertilized ponds reported from Sundarbans [4,28] and corroborated with those reported earlier by Mondal et al [29] from the same location. Lower nutrient concentrations in the studied extensive system may be attributed to complete dependence on natural productivity without any additional input.…”
Section: Discussionsupporting
confidence: 80%
“…Small fry can enter through traditional bamboo screen during water exchanges but exit of bigger fishes is restricted. As seeds of L. parsia remain available in north-east coast of India during the month of January-March [2,4,18], entry of gold spot mullet fry along with other species was anticipated. Following traditional practice, no fertilizer or supplementary feed was used and fishes grew depending on natural food.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems consistent with other trials in farmed fish, such as burbot Lota lota , Atlantic cod G. morhua and Pearl spot Etroplus suratensis (Wocher, Harsányi & Schwarz ; Björnsson et al . ; Biswas, Ghoshal, Natarajan, Thirunavukkarasu, Sundaray, Kailasam, De, Sukumaran, Kumar & Ponniah ). These results together suggest that CF and CV are less sensitive than SGR to stocking density.…”
Section: Discussionmentioning
confidence: 99%
“…37), and Etroplus suratensis fingerlings (Pearlspot; Ref. 7), revealed that diminished stocking densities yielded fish with comparably Fig. 1.…”
Section: Physiological Impacts Of High Densitymentioning
confidence: 99%